The Role of Internal Supervisor Unit (SPI) in Achieving Good University Governance: The Moderating Effect of Management Support - Adi Firman Ramadhan; Alessandra Juventini Getzevia Rumbino (Jurnal Penelitian Ekonomi dan Bisnis, 2026)
This research aims to examine the influence of the role of Internal Supervisor Unit (SPI) on the achievement of Good University Governance (GUG) principles and how management support moderating this relationship. This research uses a quantitative approach by collecting data online through a Google Form questionnaire with a total of 32 respondents who are members or part of the SPI at each Public Universities (PTN) in Indonesia. The data was analyzed using SEM-PLS with the help of WarpPLS 8.0 software. The results show that the role of Internal Supervisor Unit (SPI) empirically has a positive and significant influence on the achievement of Good University Governance (GUG) and that management support significantly strengthens the role of SPI in achieving good university governance. These findings conclude that the SPI had an important role in preventing agency conflicts that can hinder the implementation of good university governance. However, the effectiveness of the SPI’s role is greatly influenced by strong support from management. This study has limitations due to the very small number of respondents, so the results cannot be generalized to all Public Universities (PTN) in Indonesia. Further research is recommended to multiply the sample through face-to-face surveys, use a qualitative approach through interviews, and conduct comparative tests between different types of Public Universities (PTN).